2008
DOI: 10.1002/gps.1981
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in older Belgian people: comparison between people with dementia, mild cognitive impairment, and controls

Abstract: QOL of people with dementia is inferior to that of people with MCI and controls. This demonstrates the ADRQL instrument is sufficiently sensitive for evaluating the QOL of people with dementia. Longitudinal studies are needed to specifically examine the rate of QOL evolution throughout the entire dementia process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 47 publications
(72 reference statements)
8
52
2
7
Order By: Relevance
“…Studies in non-PD populations have similarly found no difference in global scores of HR-QOL between patients with MCI and normal controls [12,31,32]. While most dimensions were unaffected in these studies there were differences in select psychological dimensions, as we found in our study of PD patients.…”
Section: Discussioncontrasting
confidence: 35%
“…Studies in non-PD populations have similarly found no difference in global scores of HR-QOL between patients with MCI and normal controls [12,31,32]. While most dimensions were unaffected in these studies there were differences in select psychological dimensions, as we found in our study of PD patients.…”
Section: Discussioncontrasting
confidence: 35%
“…Two previous studies found no differences in QoL between MCI patients and healthy controls, using different instruments to evaluate QoL (Missotten et al, 2008;Ready et al, 2004). The first study used the Dementia QoL Scale (Brod, Stewart, Sands, & Walton, 1999), an instrument Notes: Scores are mean (SD).…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether QoL is already disturbed in more initial phases of cognitive decline, like Mild Cognitive Impairment (MCI), a clinical entity now accepted in both clinical practice and research that entails a high risk of progression to dementia. Some researchers found that QoL is not affected in MCI patients (Missotten et al, 2008;Ready et al, 2004) while other detected that some aspects of QoL are altered (Muangpaisan, Assantachai, Intalapaporn, & Pisansalakij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although MCI criteria continue to be refined, 4,5 the diagnostic tenet that MCI patients evidence largely intact functional abilities continues to be central. This reflects the clinical view that frank restriction in functional activities is a hallmark of AD and other dementias.…”
mentioning
confidence: 99%
“…6,7 However, an increasing number of cross-sectional studies have shown that persons with MCI experience limitations in functional abilities relative to cognitively healthy older adults. [1][2][3]8 The longitudinal course of such functional restrictions has received less attention. [9][10][11][12] Medical decision-making capacity (MDC) (also referred to as treatment consent capacity or consent capacity) is a higher-order functional capacity.…”
mentioning
confidence: 99%